Reviving Gandhara Civilization under CPEC - Dost Barrech; Dr. Samra Naz; Dr. Barket Shah Kakar; Tahira Naudhani; Ayesha Alam (Al-Qanṭara, 2023)
The Gandhara Civilization, ostensibly, holds immense significance for Pakistan, representing a great dimension of rich cultural heritage. The Gandhara civilization thrived around 1000 BC lasted for over 1000 years, currently, is located in northwestern Pakistan. It remained the centre of learning and attracted intellectual discourse. Its cosmopolitan nature and cultural fusion promoted an environment of tolerance and harmony. By showcasing archaeological sites associated with Buddhism, and highlighting the rich cultural heritage under China-Pakistan Economic Corridor CPEC, Pakistan is extremely likely to attract thousands of tourists annually. More than 535 million people practice Buddhism across the globe and the majority of them inhabit in Asia. An estimated 245 million people are practising Buddhism in China. The world’s largest numbers of Buddhist adherents are in China. The former used Buddhism as a soft power with the Southeast Asian countries reinforced its soft image in the aforementioned countries. Buddhism cemented China’s soft image. The country remains the largest Buddhist state in the world, obtaining an overwhelming soft power attractiveness among the Southeast Asian Buddhist states like Myanmar, Thailand and Sri Lanka. Pakistan has huge potential and resources under CPEC it can replicate the Chinese model by promoting Gandhara Civilization and Buddhist diplomacy resulting in promoting religious tourism, and soft power. This paper, thus, will focus on the revival of the Gandhara Civilization under CPEC. How can it pave the way for religious tourism, promoting soft power, tolerance and harmony? In this paper, mixed-method would be applied by using both primary and secondary data.